2003
DOI: 10.1007/s00401-003-0766-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of major histocompatibility complex class II-positive microglia and cytokine profile of Parkinson's disease brains

Abstract: There are numerous observations confirming that microglia expressing major histocompatibility complex (MHC) class II molecules are associated with the central nervous system (CNS) in aging and pathological conditions. In this study, we investigated the distribution of MHC class II-positive microglia in Parkinson's disease (PD) brains. The number of MHC class II-positive microglia in the substantia nigra (SN) and putamen increased as the neuronal degeneration of the SN proceeded. These cells were also ICAM-1 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
451
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(503 citation statements)
references
References 50 publications
21
451
2
5
Order By: Relevance
“…Statistical parametric mapping allows exploratory voxel by voxel group comparison throughout the entire brain volume without requiring a priori hypothesis. The authors in essence confirmed in vivo what is known from neuropathologic studies; 49 namely, that there is widespread microglial activation in the substantia nigra and basal ganglia, but also in cortical association regions (i.e., hippocampus, transentorhinal cortex, cingulated cortex), the same regions that have a high burden of Lewy body pathology in the early stages of the disease. 50 It is important to note that PD is emerging as a multisystem disease with involvement of regions outside the nigrostriatal connections and that a widely distributed tissue pathology is already present in the early clinical phase of the disease.…”
Section: Movement Disorderssupporting
confidence: 64%
“…Statistical parametric mapping allows exploratory voxel by voxel group comparison throughout the entire brain volume without requiring a priori hypothesis. The authors in essence confirmed in vivo what is known from neuropathologic studies; 49 namely, that there is widespread microglial activation in the substantia nigra and basal ganglia, but also in cortical association regions (i.e., hippocampus, transentorhinal cortex, cingulated cortex), the same regions that have a high burden of Lewy body pathology in the early stages of the disease. 50 It is important to note that PD is emerging as a multisystem disease with involvement of regions outside the nigrostriatal connections and that a widely distributed tissue pathology is already present in the early clinical phase of the disease.…”
Section: Movement Disorderssupporting
confidence: 64%
“…Thus in PD itself, α‐synuclein itself might be an antigen used by MHC II during antigen presentation and thus leading to the observed glial infiltration in PD (Hunot and Hirsch, 2003). However it has been also demonstrated that MHC II is upregulated in Parkinson brains, and was not linked to the presence of Lewy‐bodies, indicating, that α‐synuclein might only play a minor role in the recruitment of MHC II positive microglia, and invasion occurs due to the neuronal injury and the associated phagocytosis (Imamura et al, 2003; McGeer et al, 1988). …”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions the central nervous system expresses low levels of MHC II (Shrikant and Benveniste, 1996); however increases in MHC II levels have been documented in a number of pathological states including multiple sclerosis (Hofman et al, 1986) and Alzheimer's disease (Parachikova et al, 2007). Increases in MHC II‐positive cells have long been recognised in human post‐mortem tissue from PD patients (Imamura et al, 2003; McGeer et al, 1988). Also an increase in the number of MHC II‐positive microglia is seen in mice treated with 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP), a drug which induces a PD‐like disease in mice (Kurkowska‐Jastrzebska et al, 1999a, 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Overwhelmingly activated microglia are present in the vicinity of the degenerating neurons in the substantia nigra (SN) of PD patients. 3 Microglial activation can be classified into two major phenotypes defined as 'classical activation' (also termed M1 phenotype or overactivated phenotype) and 'alternative activation' (M2 phenotype). 4,5 M1 microglia polarization is associated with the production and release of multiple proinflammatory cytokines.…”
mentioning
confidence: 99%